Identification of airborne fungi isolated from Faculty of Dentistry in Universiti Teknologi MARA Sungai Buloh Campus / Nurina Hannani Hishammuddin ... [et al.] - Sarmin, Nurul ‘Izzah; Hishammuddin, Nurina Hannani; Yusof, Hartini (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Indoor airborne fungi are known to be the contributor to irritative disorders, primarily non-infective diseases such as allergy and asthma. Spores and hyphal fragments of fungi contained in bioaerosols can be breathed in easily and evoke bronchial irritation and allergy and in immunocompromised individuals, fungi can cause opportunistic infections. Therefore, the present study was undertaken to identify the airborne fungi that have been isolated from the building of Faculty of Dentistry in UiTM Sungai Buloh campus by using macromorphology, micromorphology and also molecular study. Fungi that were kept in 20% glycerol stock were subcultured on Sabouraud dextrose agar (SDA) and were observed for their macromorphological and micromorphological characteristics. The macromorphology of the fungal isolates were observed based on colour, texture and form while the micromorphology were observed for morphological structures such as phialides and metulae. Subsequently, DNA was then extracted and the internal transcribed spacer regions (ITS1-5.8S-ITS2) was amplified using forward primer ITS1 and reverse primer ITS4. One of the amplicons were sent for sequencing and was identified as Penicillium citrinum with 99% sequence similarity. In conclusion, identification of microorganisms isolated from dental building is necessary to minimise cross infection to the patients and healthcare providers.